A NEW SPECIES OF MANGIFERA (ANACARDIACEAE) - Hou, Ding (Research Center for Biology, 1972)
There are only two species of Mangifera, M. duperreana Pierre from Indochina and M. lagenifera Griff, from Malay Peninsula and Sumatra, which were described to have flowers with 10 (â12) stamens, of which 5 (or 6) are fertile. In the latest monograph of the genus by Mukherji (in Lloydia 12,1949: 73 â 136), they were placed in two different sections (without naming the sections). According to him, the floral morphology of these two species shows that they